Exploring the interplay of attachment style and attachment-related mood on short-term change in mentalization: a pilot study - Fuchs, Nikolas Fabian; Taubner, Svenja (Personality and individual differences, 2019)
Mentalization, which is the ability to attribute mental states to oneself and others underlying behavior, is an important prerequisite for surviving in social interactions. It has been shown that this particular skill not only differs between individuals with different attachment styles but can also be temporarily influenced by attachment-related stress. Based on recent empirical research, we explored the effects of positive and negative attachment-related mood inductions on mentalizing performance with attachment style as a moderating variable. Using a split-in-half “Movie for the Assessment of Social Cognition” (MASC) as a proxy for mentalization, ninety-two healthy adults were either confronted with a positive, negative or neutral attachment-related mood induction after the first half of the video-based test by letting them memorize different experiences and then proceeded with the second half. Attachment style was obtained one week later. The statistical effect of attachment style on the change in mentalization depending on the experimental condition was investigated via moderation analysis. Results showed that higher attachment anxiety was associated with significantly better mentalization performance after a positive attachment-related mood induction whereas attachment avoidance was not. The data give further evidence that attachment style plays a distinct role in short-term changes in mentalization.
Gesehen am 19.08.2019